ANALYSIS OF STUDENT DIGITAL LITERACY IN LINEAR ALGEBRA COURSES DURING THE COVID-19 PANDEMIC - Fadillah, Ahmad; Sukmawati, Rika; Rahardjo, Sigit (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
AbstrakTujuan penelitian ini untuk menganalisis dan mendeskripsikan kemampuan literasi digital mahasiswa pada matakuliah aljabar linier dengan menggunakan pembelajaran online selama pandemi Covid-19. Responden penelitian ini berasal dari mahasiswa program studi pendidikan matematika Universitas Muhammadiyah Tangerang berjumlah 30. Metode penelitian yang digunakan kualitatif deskriptif, dengan instrumen berupa angket literasi digital dengan menggunakan skala likert. Hasil penelitian menunjukan bahwa literasi digital mahasiswa memiliki rata-rata skor 75, 20 dengan kategori tinggi dengan skor rata-rata indikator kemampuan mengoperasikan komputer 82.00, kemampuan membangun informasi 70.00, memanfaatkan akses internet 72.00, menyajikan informasi 74.00, serta kemampuan berkomunikasi dan publikasi 78.00.Â Kata kunci: Aljabar Linier; Covid-19; Literasi DigitalÂ AbstractThe purpose of this study is to analyze and describe the ability of students' digital literacy in linear algebraic courses using online learning during the Covid-19 pandemic. Respondents to this study came from students of mathematics education program University of Muhammadiyah Tangerang numbered 30. The research method used qualitative descriptive, with instruments in the form of digital literacy questionnaires using a likert scale. The results showed that students' digital literacy has an average score of 75. 20 with a high category with an average score of the ability indicator ability to operate a computer 82.00, Ability to build information 70.00, Take advantage of internet access 72.00, Present information 74.00, and Ability to communicate and publish 78.00.Â Keywords: Covid-19; Digital Literacy; Linear Algebra